Efektifitas Aktifitas Fisik Jalan Kaki terhadap Tingkat Stress pada Remaja - Lilik Pranata; Vincencius Surani; Novita Elisabeth Daeli; Sri Indaryati; Srimiyati Srimiyati (STIKES Columbia Asia Medan, 2025)
Global data shows that more than 60% of adolescents report experiencing moderate to severe stress due to academic and social demands. Physical activity plays an important role in maintaining adolescent mental health. Regular physical activity can stimulate the release of endorphins, improve cognitive function, reduce muscle tension, and reduce levels of cortisol, the main hormone associated with stress. One of the easiest, cheapest, safest, and most accessible forms of physical activity is walking. Walking is a moderate-intensity aerobic activity that has been proven to improve mood, improve sleep patterns, and reduce anxiety. The purpose of this study was to determine the effectiveness of walking as a physical activity on stress disorders in adolescents. The research method used a quasi-experimental design with a pretest-posttest control group approach, involving 44 participants, comprising 22 intervention and 22 control subjects. The walking activity was conducted for three consecutive days, with a duration of 60 minutes, from 16:00 to 17:00 WIB, on 16-18 December 2024. The sample criteria were first-year nursing students in their first semester who performed walking activities continuously for three days. The results showed a significant difference in stress levels before and after the intervention, with a significance level of (Z=-3.557, p=0.000). This means that there was a significant difference in stress levels between before and after the physical activity intervention. The difference in stress levels before and after the intervention in the control group was significant (Z=-1.000, p=0.317). This means that there was no difference in stress levels in the control group. The difference in stress levels between the intervention group and the control group after treatment was significant (Z=-3.445, p=0.001). This indicates that there is a significant difference in stress levels between the intervention group and the control group after the physical activity intervention. Walking is an effective, affordable, and feasible intervention for the adolescent population as a promotive and preventive strategy in stress management.